Biofuel: Concepts and Considerations - Tanumoy Bera; Kanika S. Inglett; Ann C. Wilkie (EDIS)
Biofuels are combustible fuels derived from recently produced biomass, as opposed to ancient biomass, which is the source of petroleum products. The term biofuel usually refers to liquid fuels used as replacements for or additives to petroleum-based liquid fuel. This new 6-page publication of the UF/IFAS Department of Soil and Water Sciences serves as an introduction to biofuels for Extension educators and anyone interested in learning basic terminology, concepts, and impacts of biofuels as a replacement for fossil fuels. Written by Tanumoy Bera, Kanika S. Inglett, and Ann C. Wilkie. https://edis.ifas.ufl.edu/ss688